Pharmacokinetic–pharmacodynamic modelling of platelet response to ticagrelor in stable coronary artery disease and prior myocardial infarction patients. Issue 2 (18th December 2018) - Åstrand, Magnus; Amilon, Carl; Röshammar, Daniel; Himmelmann, Anders; Angiolillo, Dominick J.; Storey, Robert F.; Gurbel, Paul A.; Bonaca, Marc P.; Hamrén, Bengt
Abstract : Aims: To characterize ticagrelor exposure‐response relationship for platelet inhibition in patients with stable coronary artery disease (CAD) and a history of myocardial infarction (MI), using nonlinear mixed effects modelling and simulation. Methods: Platelet function data were integrated with plasma concentration data of ticagrelor and its active metabolite AR‐C1249010XX in a population pharmacokinetic (PK) and pharmacodynamic (PD) model, based on two clinical studies. In the ONSET/OFFSET study, PK and platelet function were assessed in 123 CAD patients receiving placebo, ticagrelor (180 mg followed by 90 mg twice daily) or clopidogrel (600 mg followed by 75 mg once daily). In the PEGASUS‐TIMI 54 platelet function substudy, PK and platelet function were assessed during maintenance dosing in 180 prior MI patients receiving placebo, ticagrelor 60 mg or ticagrelor 90 mg twice daily. Results: Platelet inhibition by ticagrelor was described by a sigmoidal Emax model. On average, half maximal inhibition was reached at ticagrelor concentrations of 116 (RSE: 5.3%) nmol l –1 . Simulations showed that near maximal platelet inhibition is achieved with both ticagrelor 60 and 90 mg twice daily. At simulated lower doses, platelet inhibition is overall reduced, more variable between patients, and show greater peak‐to‐trough variability. Ticagrelor antiplatelet response was similar between the studied patient populations. Conclusions: In patients with stable CAD or a history of MI, near maximal platelet inhibition is achieved with both ticagrelor 60 and 90 mg twice daily. At modelled doses <60 mg, the response is reduced overall, more variable between patients, and patients will display greater peak‐to‐trough variability.